Antibiotic resistance patterns of pediatric community-acquired urinary infections - Guidoni,Eliana Biondi Medeiros (2008)
Knowledge about antimicrobial resistance patterns of the etiological agents of urinary tract infections (UTIs) is essential for appropriate therapy. Urinary isolates from symptomatic UTI cases attended at Santa Casa University Hospital of São Paulo from August 1986 to December 1989 and August 2004 to December 2005 were identified by conventional methods. Antimicrobial resistance testing was performed by Kirby Bauer's disc diffusion method. Among the 257 children, E. coli was found in 77%. A high prevalence of resistance was observed against ampicillin and TMP/SMX (55% and 51%). The antibiotic resistance rates for E. coli were: nitrofurantoin (6%), nalidixic acid (14%), 1st generation cephalosporin (13%), 3rd generation cephalosporins (5%), aminoglycosides (2%), norfloxacin (9%) and ciprofloxacin (4%). We found that E. coli was the predominant bacterial pathogen of community-acquired UTIs. We also detected increasing resistance to TMP/SMX among UTI pathogens in this population.